Pengembangan Media Pembelajaran IPA Menggunakan Macromedia Flash 8 Berbasis Model Discovery Learning Untuk Meningkatkan Hasil Belajar Kognitif Tingkat Tinggi Di Kelas IV SD - Leo Azmi, Yoan; Widi Winarni, Endang; Parmadi, Bambang (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this study is to develop, describe the characteristics, logical feasibility, user response and effectiveness of learning media using Macromedia Flash 8 based on discovery learning to improve high-level cognitive learning outcomes of grade IV students of elementary school 06 Seluma. The type of research used is R&D (Research and Development) research with the ADDIE development model. The types of data used are qualitative and quantitative data using instruments in the form of interviews, needs analysis questionnaires, expert validation sheets, and user response questionnaires. The results of the study indicate that Macromedia Flash 8 learning media is able to improve student interactivity. Logically, the Macromedia Flash 8 learning media is feasible to use based on the results of the material validation of 0.95 language experts 0.95 media/design experts 1.0 which is a high validity category. User responses show a percentage of 100% of the attractiveness of the Macromedia Flash 8 learning media. The effectiveness of the Macromedia Flash 8 learning media is very high, this is indicated by the average of the N-Gain test of 85.65 or 86% which is included in the effective category. So it can be concluded that the use of Macromedia Flash 8 learning media can improve the high-level cognitive learning outcomes of grade IV students of SD Negeri 06 Seluma.